Antigen‐specific over‐expression of human cartilage glycoprotein 39 on CD4+CD25+ forkhead box protein 3+ regulatory T cells in the generation of glucose‐6‐phosphate isomerase‐induced arthritis. (August 2014) - Tanaka, Y.; Matsumoto, I.; Inoue, A.; Umeda, N.; Takai, C.; Sumida, T.
Summary Human cartilage gp‐39 (HC gp‐39) is a well‐known autoantigen in rheumatoid arthritis (RA). However, the exact localization, fluctuation and function of HC gp‐39 in RA are unknown. Therefore, using a glucose‐6‐phosphate isomerase (GPI)‐induced model of arthritis, we investigated these aspects of HC gp‐39 in arthritis. The rise in serum HC gp‐39 levels was detected on the early phase of GPI‐induced arthritis (day 7) and the HC gp‐39 mRNA was increased significantly on splenic CD4+T cells on day7, but not on CD11b+cells. Moreover, to identify the characterization of HC gp‐39+CD4+T cells, we assessed the analysis of T helper (Th) subsets. As a result, HC gp‐39 was expressed dominantly in CD4+CD25+ forkhead box protein 3 (FoxP3)+ refulatory T cells (Treg), but not in Th1, Th2 or Th17 cells. Furthermore, to investigate the effect of HC gp‐39 to CD4+T cells, T cell proliferation assay and cytokine production from CD4+T cells using recombinant HC gp‐39 was assessed. We found that GPI‐specific T cell proliferation and interferon (IFN)‐γ or interleukin (IL)‐17 production were clearly suppressed by addition of recombinant HC gp‐39. Antigen‐specific over‐expression of HC gp‐39 in splenic CD4+CD25+ FoxP3+ Treg cells occurs in the induction phase of GPI‐induced arthritis, and addition of recombinant HC gp‐39 suppresses antigen‐specific T‐cell proliferation and cytokine production, suggesting that HC gp‐39 in CD4+ T cells might play a regulatory role in arthritis.